A Model for Commercialization Strategies Success in Marketing in Iran: A Case Study of Industrial Companies in Tehran - Farzad Fakhr (International Journal of Management, Accounting and Economics, 2021)
Commercialization strategy is one of the most crucial decisions a firm makes in terms of its ability to profit from technologies developed within the firm. This study was carried out to propose a model for commercialization strategies success in marketing in Iran. This study was a descriptive survey and the survey instrument was a researcher-made questionnaire. Statistical society was all of managers in industrial companies of Tehran. Statistical society was all of managers in industrial companies of Tehran. Sample size (245 persons) determination is based on the Krejcie & Morgan table and cluster random sampling method was used. After data collection, data analysis was performed using Statistical Package for the Social Sciences (SPSS). Reliability of research tool was calculated by Cronbach's alpha and the value of that was 0.81. Results and finding of this research showed that government policy, Legal restrictions and Organizational difficulties affect commercialization strategies success in marketing in Iran.